1999
DOI: 10.1016/s0378-1097(99)00223-2
|View full text |Cite
|
Sign up to set email alerts
|

The respiratory burst-inhibiting acid phosphatase AcpA is not essential for the intramacrophage growth or virulence of Francisella novicida

Abstract: Acid phosphatases capable of inhibiting the respiratory burst of neutrophils have been identified in certain intracellular pathogens. Here we evaluate the role of AcpA, a respiratory burst-inhibiting acid phosphatase of Francisella, in the virulence and intracellular growth of this organism. An F. novicida acpA null mutant was created and found to exhibit wild-type growth kinetics in both cell-line and inflammatory mouse macrophages. The acpA mutant also shows wild-type replication in the spleens of experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 12 publications
(34 reference statements)
1
26
1
Order By: Relevance
“…AcpA is proposed to be involved in inhibition of the respiratory burst (Reilly et al, 1996), but recently phospholipase activity has also been proposed for AcpA, with a role in phagosomal trafficking of the bacterium (Felts et al, 2006;Mohapatra et al, 2007). However, there are conflicting reports on whether AcpA is essential for virulence and intracellular replication (Baron et al, 1999;Mohapatra et al, 2007), which are yet to be resolved. DnaK was first demonstrated to be upregulated in macrophages using a proteomic approach (Golovliov et al, 1997) and was identified as being essential for intracellular growth and virulence of subsp.…”
Section: Resultsmentioning
confidence: 99%
“…AcpA is proposed to be involved in inhibition of the respiratory burst (Reilly et al, 1996), but recently phospholipase activity has also been proposed for AcpA, with a role in phagosomal trafficking of the bacterium (Felts et al, 2006;Mohapatra et al, 2007). However, there are conflicting reports on whether AcpA is essential for virulence and intracellular replication (Baron et al, 1999;Mohapatra et al, 2007), which are yet to be resolved. DnaK was first demonstrated to be upregulated in macrophages using a proteomic approach (Golovliov et al, 1997) and was identified as being essential for intracellular growth and virulence of subsp.…”
Section: Resultsmentioning
confidence: 99%
“…However, acpA-null mutants of F. tularensis subsp. novicida are not attenuated in mice (15). Thus, resistance to toxic oxidants may be multifactorial.…”
Section: Role Of Neutrophilsmentioning
confidence: 97%
“…Two studies found that AcpA is required for replication of F. novicida in human macrophage-like cells, indicating that blocking the NADPH oxidase is an important factor in facilitating replication (11,155). In contrast, another study using F. novicida determined that AcpA did not play a role in replication in murine macrophages (22). In F. tularensis, deletion of acpA, or even of acpA, acpB, and acpC together, did not influence virulence in murine macrophages or human monocytes (48,146).…”
Section: Inhibition Of Reactive Oxygen Speciesmentioning
confidence: 99%